A photovoltaic model based method to monitor solar array degradation on-board a microsatellite - Soon, Jing Jun (2020)
The lifespan of a microsatellite depends on the adequate power obtained from its solar array. Hence, it is important to monitor the degradation of the solar array in-orbit as uncertain activities of the Sun would change the space radiation environment. To monitor the degradation, a degradation model together with a space environmental model is typically used. In this paper, an alternate method to monitor the solar array degradation of a satellite using a photovoltaic model as a reference is proposed. The proposed method can be used on any satellite with its voltage, current, incidence angle, and temperature of the solar array known. From the results, the proposed method shows that the solar array of X-SAT has a higher rate of degradation from January 2012 to March 2012 due to extreme space weather event. Moreover, the degradation for the Y + and Y - deployable solar panels over the first three years is 28.40% and 41.52%, respectively.